Mining Community Development Agreements : Source Book - World Bank (Washington, DC, 2013)
The World Bank oil, gas and mining unit, in its capacity as a driver for best practice related to extractive industry contributions to poverty alleviation, has a strong interest in the sustainable development of mine-impacted communities. As part of the growing global expectation that the extractive industry should contribute positively to long-term local development, a discourse has grown surrounding a variety of structures and processes aiming to deliver development benefits to communities affected by mineral resource projects. Examples of these strategies include social/community investment programs, development forums, community-controlled trusts, development funds, and foundations. These strategies may be led by government, the companies, the impacted community, or through collaborative bilateral or multi sector partnerships and agreements. They may be a regulatory requirement or negotiated voluntarily in response to mining companies' commitment to corporate social responsibility (CSR) principles. This document describes some of the main considerations and processes regarding the development and implementation of these strategies, specifically in relation to Community Development Agreements (CDAs). In the last few years the World Bank oil, gas and mining unit has worked to analyze CDAs within the mining sector as an instrument for more sustainable and equitable benefits. This process of analysis and research has involved a series of reports by the World Bank and external specialists aiming to provide technical input on the process, case studies, lessons learned, and best practices for CDA development. This report builds on previous studies to deliver a knowledge product on CDA development with the aim of providing specific assistance to the process and delivery of CDAs. This source book has been developed from learnings relating to existing regulations/ requirements, past experiences, and case studies. Volume 2 contains the World Bank Extractive Industries Sourcebook, Good Practice Notes: Community Development Agreements, and Volume 3 is the Mining Community Development Agreements - Practical Experiences and Field Studies. Volume 4 is the Community Development Agreement - Model Regulations and Example Guidelines.